Medicina de sistemas: uma abordagem holística, estratégica e institucional para a gestão da manutenção - Arcuri Filho, Rogério (2005)
This study deals with the maintenance function management and the challenges that it has been called upon to respond as a result of intricate scenarios being nowadays faced by all organizations in search for survival and perennial continuity. Taking into account these concerns the study analyzes the problems related to organizational sustainability proposing a holistic model of integrated maintenance management system that can contribute to the excellence in corporate performance. Based upon a broad revision of the related literature a theoretical reference has been established to investigate the practices concerning the usual policies for maintenance management followed by the description of a new conceptual management model for the activity with more extensive and integrated characteristics to be settled in complement to those traditionally used. This model is called "systems medicine" in an analogy to medicine herein considered the "maintenance of the human being". Closing the study suggestions for future approaches regarding the subject are also presented such as the generic principles for a national maintenance policy included in a strategic institucional vision for the activity